Bilateral Otic Manifestation of Pseudogout: A Unique Case Report of Conductive Hearing Loss - Svejdova, Anna; Homolac, Michal; Krtickova, Jana; Laco, Jan; Mejzlik, Jan; Dedkova, Jana; Drsata, Jakub; Skoloudik, Lukas; Bradna, Petr; Chrobok, Viktor (The Laryngoscope, 2024)
Pseudogout is characterized by the deposition of calcium pyrophosphate dihydrate crystals (CPPD), primarily affecting large joints. Extra-articular manifestations, particularly in the head and neck region, are exceedingly rare. We report a unique case of bilateral isolated pseudogout of the middle ear manifesting with progressive conductive hearing loss as the first and only symptom of pseudogout. Otoscopy and CT scan often yield a differential diagnosis that includes tumors or cholesteatoma, necessitating surgery with histopathological examination. The definitive diagnosis is confirmed upon identification of calcium pyrophosphate dihydrate crystals. In most cases, removal of the crystals results in resolution of conductive hearing loss. Laryngoscope, 134:5131-5134, 2024.
Keywords: lidé; Middle Aged; chondrokalcinóza; otoskopie; diferenciální diagnóza; počítačová rentgenová tomografie; Female; střední ucho; Ear, Middle; Humans; Otoscopy; Chondrocalcinosis; lidé středního věku; mužské pohlaví; ženské pohlaví; Diagnosis, Differential; Tomography, X-Ray Computed; Male; Hearing Loss, Conductive; převodní nedoslýchavost